2010
DOI: 10.1007/bf03214985
|View full text |Cite
|
Sign up to set email alerts
|

Printed gold for electronic applications

Abstract: Molecular and nanoparticulate gold precursors for application in inkjet printing onto flexible substrates are discussed. The choice of stabilising ligands and the size of the nanoparticles influence the solution stability of the ink and their ability to form decorative or conductive functional films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Gold metal is a highly effective corrosion-resistive material due to its high electrical and thermal conductivity. Thin films and nanomaterials of gold have found some wide range applications such as in optical devices [4,6,8], power sources [151], microelectronic devices [2][3][4][5][6][7][8][9][10] and so on. In the end of last century, Haruta et al [152][153][154] have revealed that gold nanoparticles with diameters less than 10 nm, uniformly dispersed in metal oxides exhibit high catalytic activity in the reaction of CO oxidation at low temperature.…”
Section: Applications Of Volatile Compound Of Gold In Cvd/ald Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold metal is a highly effective corrosion-resistive material due to its high electrical and thermal conductivity. Thin films and nanomaterials of gold have found some wide range applications such as in optical devices [4,6,8], power sources [151], microelectronic devices [2][3][4][5][6][7][8][9][10] and so on. In the end of last century, Haruta et al [152][153][154] have revealed that gold nanoparticles with diameters less than 10 nm, uniformly dispersed in metal oxides exhibit high catalytic activity in the reaction of CO oxidation at low temperature.…”
Section: Applications Of Volatile Compound Of Gold In Cvd/ald Processesmentioning
confidence: 99%
“…Interest in the chemistry of volatile compounds of gold is associated, primarily, with the growing demand for Metal Organic Chemical Vapor Deposition (MOCVD) precursors used in the process of growing gold thin films and nanoparticles. Due to their low resistivity and high corrosion stability thin films and nanomaterials of gold find numerous valuable applications as in anticorrosion coatings [1], films in optical and microelectronic devices [2][3][4][5][6][7][8][9][10], protective layers for inner surfaces of microwave waveguide resonators [11,12], electrical contacts and interconnects and layers in solar batteries [13]. Furthermore, they find application in electrochemical and biomedical applications [14], in the areas of organic synthesis and catalysis [15,16], photophysics, photochemistry [17][18][19] and in chemotherapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To date, a variety of device fabrication methods using this technique have been proposed, including those for the fabrication of electrooptic devices, 35 gas sensors, 68 electrochromic devices (ECDs), 9 interconnections for circuitry on a printed-circuit board (PCB), 10 thin-film transistors (TFTs), 11 organic light-emitting diodes (OLEDs), 12 large-area displays, 13 and radio frequency identification (RFID) tags. 14,15 For patterning electrodes and wires of the devices, metal nanoparticles, such as Au, 1517 Ag, 18,19 and Cu 20,21 have been studied as promising ink particles, since the particles exhibit good dispersibility in solvents through coating of the particle surfaces with organic monolayers, and they form flexible films with high metal content after being cured.…”
Section: ¹1mentioning
confidence: 99%
“…Printing technology has been gradually forward to unconventional, such as microcontact printing (μCP) [13][14][15], and ink-jet print [16][17][18], these print method always combines with electorless deposition, by controlling the position of activation place can selective decide the metal crystals grow and deposition. Electroless deposition is a stable and has been used in many process, this method without high cost equipment, and deposition at low temperature [9][10][11][12] is commonly used as a way. The general process of electroless deposition involves preparation of surface, activation by catalyst metal particaleson desire place, and immersed in electroless bath to deposition metal on the substrate, then metallization on the non-conductive substrate.…”
Section: Introducsionmentioning
confidence: 99%